A preliminary study of the reliability and validity of the Uyghur version of the NUCOG cognitive screening application - Nazuk Yusup; Altunsa Rahmat; Hongyan Li (BMC Neurology)
Abstract Introduction Technological advances and artificial intelligence now make it feasible to administer cognitive assessments on touch-screen devices. The aim of this study is to develop a Uyghur version of the NUCOG cognitive screening application and evaluate its reliability, validity, and optimal cutoff scores among Uyghur people with cognitive impairment. Methods The English version of the NUCOG app was translated and adapted into the Uyghur version (NUCOG-U). A total of 250 Uyghur people aged 55–80, including 90 normal controls, 91 patients with mild cognitive impairment (MCI), and 69 dementia patients, were randomly selected and administered with NUCOG, MoCA-U, Mini-Mental State Examination (MMSE), and other neuropsychological batteries. ROC curves were generated to determine the optimal cutoff values. Results NUCOG-U version showed high internal consistency (Cronbach’s α = 0. 826), inter-rater reliability (ICC = 0.999), and test − retest reliability (r = 0.998, p < 0.001). NUCOG scores were significantly correlated with those of MoCA-U (r = 0.896, p < 0.001) and MMSE(r = 0.899, p < 0.001). NUCOG scores were significantly different among the three groups (p < 0.001). The optimal cutoff value for MCI was 80.5, with a sensitivity of 100% and specificity of 73%, and 70 for dementia, with a sensitivity of 94.1% and specificity of 100%. Conclusion The NUCOG-U shows high reliability and validity and is suitable for screening cognitive function in the elderly Uyghur population. The optimal cutoff scores to detect mild cognitive impairment and dementia in the Uyghur people are 80.5 and 70, respectively.